An Investigation of the Dissipation Kinetics of Picloram Herbicide Residues in Lake Water Under Climatic Conditions using a Validated High-Performance Liquid Chromatography with a Photodiode Ar - Prashanthi, Y. (Asian Journal of Pharmaceutics (AJP), 2025)
Understanding the dissipation kinetics of the picloram herbicide is crucial for assessing its environmental impacts and persistence in aquatic ecosystems. Materials and Methods: An experiment was conducted to observe the dissipation behavior of picloram in lake water by introducing uniform concentrations: T0 – Untreated Control, T1 – picloram 24% soluble liquid (SL) at 1 μg/mL, and T2 – picloram 24% SL at 2 μg/mL. The spiked samples were exposed to sunlight. Water samples were collected at various intervals (0.5, 1, 3, 5, 10, 15, and 30 days). All samples were analyzed until the residues fell below the detectable level. The quantification of picloram residues was performed using a validated high-performance liquid chromatography with a photodiode array detector (HPLC-PDA) at a wavelength of 235 nm. Results and Discussion: The method’s limit of detection was 0.015 μg/mL, and the limit of quantification (LOQ) was 0.05 μg/mL based on recovery. The DT50 (Half- Life) of picloram was calculated through regression analysis of the dissipation data, yielding a DT50 value of 6.63 days for the T1 dose and 6.60 days for the T2 dose. Conclusion: This study outlines a rapid HPLC-PDA method for quantifying picloram residues in buffers, utilizing a mobile phase of acetonitrile and 0.1% ortho- phosphoric acid for separation in about 10 min. Validation followed South African National Civic Organization and Environmental Protection Agency guidelines, ensuring satisfactory parameters such as linearity, recovery, precision, and LOQ. The method is applicable for routine monitoring in crops, water, and soil.